Dampak Kualitas Udara Terhadap Keluhan Kesehatan Karyawan Gardu Tol Slipi 2 dan Tanjung Duren PT. Jasa Marga (Persero) Tbk - Ramadhan, Taufan; Wadji, Farid; Kusmasari, Wyke (Universitas Serang Raya, 2016)
The use of technology and transportation to meet human needs that are increasingly complex turns out to cause various environmental problems. One of the problems caused is air pollution due to motor vehicle exhaust emissions. This study aims to determine the impact of air pollution on the health of employees guarding the substation of Slipi 2 toll road and Tanjung Duren Jakarta. Data were taken from respondents using the questionnaire survey method and the Impinger Air Sampler for measuring NO2 and SO2 levels. Sampling is by the number of employees of Slipi 2 toll booths and Tanjung Duren, as many as 32 people. Of the 32 respondents almost all experienced subjective complaints arising from NO2 and SO2 gas. Based on statistical tests using SPSS with Two Way ANOVA method that has been done shows that health complaints are affected by NO2, SO2, and work locations. Based on the results of the data processing interaction test using the SPSS program shows the interaction between the influence of NO2 or SO2 and the work location.